In-depth investigation of corrosion inhibition mechanism: computational, electrochemical, and theoretical studies of vanillin meldrum’s acid on mild steel surface in 1 M HCl - Kamarul Baharin, Nur Aiman Najwa; Sheikh Mohd Ghazali, Sheikh Ahmad Izaddin; Sirat, Siti Syaida; Mohd Tajuddin, Amalina; Pungot, Noor Hidayah; Abdullah, Erna Normaya; Mohd Kamarudin, Siti Radiah; Dzulkifli, Nur Nadia (Elsevier, 2024)
Vanillin Meldrum’s acid (VanMA) was successfully synthesized and thoroughly examined using techniques like elemental analysis, FTIR, NMR, UV–Vis spectroscopies, and single crystal X-ray diffraction. It crystallizes in a triclinic crystal system under the P-1 space group. A quantitative analysis of the intermolecular interactions in the crystal structures was performed using Hirshfeld surface analysis, which reveals that H⋅⋅⋅H contacts are the most significant contributing 43.2 % and the O⋅⋅⋅H/H⋅⋅⋅O contacts contributing 36.2 % of the total Hirshfeld surfaces. VanMA proved effective as a corrosion inhibitor in 1 M HCl, demonstrating a 62.19 % inhibition efficiency at an optimal concentration of 0.1 mM. It creates a protective layer on mild steel surfaces, adhering to the Freundlich adsorption isotherm (R2 = 0.9983) and displaying a physical adsorption mechanism ( 12.72 kJ/mol). The corrosion inhibition efficacy of VanMA (0.1 mM) decreases in 1 M HCl as the temperature increases from 303 to 383 K. A shift towards physisorption is indicated by the increase in activation energy (Ea) from 12.37 to 16.42 kJ/mol. VanMA’s adsorption efficacy reduces at higher temperatures, increasing surface exposure and corrosion rates, but increasing activation enthalpy (ΔH◦ = 31.32 kJ/mol) and ΔS◦ = 113.63 J mol 1 K 1). The diameter of the semicircle rose as the concentration of VanMA increased, indicating that VanMA adsorption is responsible for the mild steel surface’s greater resistance to corrosion with increasing Rct values from 224 to 641 Ω cm2 and decreasing capacitance double layer (Cdl) values from 4.480 × 10 5 to 1.560 × 10 5 μFcm2, confirming VanMA’s efficacy as a corrosion inhibitor at 65.05 %. The SEM-EDX and AFM images show the smoother mild steel surface at 0.1 mM VanMA. VanMA was verified as a mixed-type inhibitor by showing shifts of less than 85 mV with respect to the blank PDP. The inhibition efficiency (IE%) increased up to 77.89 % while the icorr values decreased to 1.1850 × 10 5 A/cm2 as the VanMA concentration rose. In XPS, the presence of VanMA was identified by the presence of FeO (713.60 eV) and C––O (287.93 eV), which signifies the adsorption of VanMA onto mild steel by the O atom and the negatively charged O ion via a mixed adsorption. DFT and Mulliken population analysis deduced that the VanMA interacted with the mild steel through mixed adsorption. VanMA adsorbs almost parallel to the Fe (1 1 0) surface, forming a barrier that protects from corrosion, according to the MD modeling. While the significant negative adsorption energy ( 309.490 kcal/mol) verifies the stability and spontaneity of the adsorption process.